Um método para avaliação de fatores de risco em cadeia de suprimentos na implementação da estratégia omnichannel - Mello, Matheus Soares Brum de (2023)
Technological advances and constant changes in purchasing habits, especially in the online environment, with direct channels to the consumer and information technology, have allowed changes in the traditional structure of supply chains. In this context, the omnichannel strategy emerges, which allows the full integration of consumer contact channels, creating a perfect shopping experience for all sales channels, based on the convergence between online and offline retail operations. Given that such a strategy can influence and, consequently, put supply chains at risk, the main question underlying this dissertation is how to assess supply chain risk factors in implementing an omnichannel retail strategy. In this sense, this dissertation sought to identify the risk factors in supply chains contemplated in the implementation of the omnichannel strategy and to develop a method of evaluating such factors, presenting the following structure: (i) to carry out a systematic review of the literature, focusing on the identification of risk factors associated with the total interaction strategy of consumer contact channels; (ii) clarify the identified risk factors; (iii) analyze qualitatively, based on consultation with specialists, focusing on understanding the agreement regarding the risk factors identified in the literature in the conception of professionals and academics in the field of logistics/supply chain and omnichannel in Brazil; (iv) develop a methodology for assessing risk factors associated with the scenario of implementing an omnichannel strategy, based on the Analytic Hierarchy Process (AHP) tool; and (v) apply the method through multiple case studies with a retailer and an industry. From the results, 10 risk subtypes were identified, including 61 risk factors, highlighting that the areas most exposed to risk are logistics/storage and processes/operations. In addition, it was also possible to detect the risk factors related to problems with fleets and vehicle routing, failures in reverse logistics, attention to logistical costs, adequacy of the organizational mindset, and development of human skills in omnichannel, which are the most sensitive to organizations' respondents. There are implications of this study both in the academic environment and at the managerial level, enabling the understanding of the strategy, its options for use, identification of subtypes and risk factors, perception of specialists in the area about the identified risk factors, clarifications, particularities, impacts on supply chain and prioritization of risk factors from a retailer and industry perspective.